A Move-based analysis of the conclusion sections of research articles published in International and Thai journals - Wirada Amnuai,; Anchalee Wannaruk, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2013)
This paper reports on an analysis of the conclusion sections of English research articles published in Thai and international journals. A comparison was made between 20 conclusion sections in international journals and 20 conclusion sections in Thai journals written by Thai writers in the field of applied linguistics. The two corpora were analysed using Yang and Allison’s (2003) move model. The results revealed that all three moves of the proposed model occurred in the two sets of data but with differences in their frequency of occurrence. There were no obligatory moves or steps in the two corpora. Move structures in the conclusion sections of the Thai corpus varied more from the proposed model than those of the conclusion sections in the international corpus. The findings could assist considerably in an understanding of the rhetorical move structure of the conclusion sections of research articles. In addition, they may yield implications for a pedagogical framework for the teaching of academic writing, syllabus design, and genre-based teaching and writing.